Numerical Analysis of Wave Run-up Characteristics on Dual Non-submerged Vertical Cylinders. Issue 3 (October 2020) - Ni, Yunlin; Shen, Yuan; Zhang, Yang; Yang, Hanbing; Li, Yanming
Abstract: In this paper, a numerical model is set up to solve the mild slope equation proposed by Berkhoff using the finite element method. The computational result of wave run-up on a single non-submerged vertical cylinder matches well with the analytical solution, verifying the validity of the numerical model. The effect of the spacing between two cylinders on wave run-up is discussed. The results show that the position of maximum and minimum wave run-up on the upstream cylinder is almost the same with that of a single cylinder, but when the spacing is odd or even times of one quarter of incident wavelength, the secondary maximum or minimum wave run-up appears at the both sides of the cylinder. The curves of wave run-up on the downstream cylinder is similar but smaller than that of a single cylinder.